Gabon : Statistical Annex. (IMF Staff Country Reports; Country Report ;, 2000)
The statistical data on gross domestic product, supply and use of resources, savings and investment balances, crude oil production and prices, capital expenditure and oil exploration, production and export of timber, livestock, fishing, production and consumption of refined oil products, transportation, and accounts of the corporate sector of Gabon have been presented. The paper also presents statistics of fiscal operations of the central government, monetary survey, international reserves, effective exchange rate, consumer price indices, and other related economic indices of Gabon.